Sources of resistance to major castor (Ricinus communis L.) diseases - Anjani, K.=700 1 Raoof, M.A.; Ashoka Vardhana Reddy, P.; Hanumanta Rao, C.
(En, Es, Fr)
ilus., 4 ref.
Keywords: RICINUS COMMUNIS; FITOMEJORAMIENTO; GERMOPLASMA; BOTRYTIS; RESISTENCIA A LA ENFERMEDAD; FUSARIUM; MACROPHOMINA PHASEOLINA; ITALIA